THE ROLE OF PRICE, PRODUCT QUALITY AND ELECTRONIC WORD OF MOUTH ON REPEAT PURCHASE DECISIONS ON GACOAN NOODLE PRODUCTS IN MALANG CITY - Amalia, Fitri; Putri, Kartika Anggraeni Sudiono (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study aims to determine the role of price, product quality and electronic word of mouth on repeat purchase decisions on Mie Gacoan products in Malang City. In this research, the type of research used is descriptive quantitative. This research was conducted on consumers of Mie Gacoan in Malang City. The sample used is 130 respondents. Data analysis using multiple linear regression analysis. The results showed that price had a positive and significant effect on repeated purchase decisions on Mie Gacoan products in Malang City, product quality had a positive and significant effect on repeated purchase decisions on Mie Gacoan products in Malang City and electronic word of mouth had an effect but not significant on purchase decisions repeated on Mie Gacoan products in Malang City.